Alcohol consumption pattern and risk of Barrett's oesophagus and erosive oesophagitis: an Italian case–control study. Issue 8 (8th May 2017) - Filiberti, Rosa A.; Fontana, Vincenzo; De Ceglie, Antonella; Blanchi, Sabrina; Grossi, Enzo; Della Casa, Domenico; Lacchin, Teresa; De Matthaeis, Marina; Ignomirelli, Orazio; Cappiello, Roberta; Rosa, Alessandra; Foti, Monica; et al.
Abstract: Knowledge about the association between alcohol and Barrett's oesophagus and reflux oesophagitis is conflicting. In this case–control study we evaluated the role of specific alcoholic beverages (red and white wine, beer and liquors) in 339 Barrett's oesophagus and 462 oesophagitis patients compared with 619 endoscopic controls with other disorders, recruited in twelve Italian endoscopic units. Data on alcohol and other individual characteristics were obtained from structured questionnaires. No clear, monotonic significant dose–response relationship was pointed out for red wine. However, a generalised U-shaped trend of Barrett's oesophagus/oesophagitis risk due to red wine consumption particularly among current drinkers was found. Similar results were also found for white wine. Liquor/spirit consumption seemed to bring about a 1·14–2·30 risk excess, although statistically non-significant, for current Barrett's oesophagus/oesophagitis drinkers. Statistically significant decreasing dose–response relationships were found in Barrett's oesophagus for frequency and duration of beer consumption. Similar, but less clear downward tendencies were also found for oesophagitis patients. In conclusion, although often not statistically significant, our data suggested a reduced risk of Barrett's oesophagus and oesophagitis with a low/moderate intake of wine and beer consumption. A non-significant increased risk of Barrett's oesophagus/oesophagitis was observed with a higher intake of any type of heavy alcohol consumption, but no conclusion can be drawn owing to the high number of non-spirit drinkers and to the small number of drinkers at higher alcohol intake levels.